Brain Oxygenation in Post-concussion Combat Sport Athletes - Tiberini, Paolo; D'Antona, Giuseppe; Cicchella, Antonio (Frontiers in Sports and Active Living, 2021)
Purpose: Investigate the feasibility of a non-invasive method to evaluate the physical and cognitive repercussions of long-lasting post-concussion effects in professional combat sports athletes. To help athletes return to professional combat, there is a need for unbiased objective tools and techniques used as a prognostic method of recovery after Sport Related Concussion (SRC). Methods: Six mild Traumatic Brain Injury (mTBI) athletes, age 20 ÷ 43 yr (1 female, 5 males) and 7 not concussed (NC) participants (amateur), age 24 ÷ 38 yr (3 females, 4 males), were tested Inspired/expired gas concentration, Cerebral changes in oxygenated hemoglobin (Δ[HbO2]) and deoxygenated hemoglobin (Δ[HHb]) were measured using near infrared spectroscopy (NIRS) with a 3-step protocol: rest before maximal oxygen uptake (VO2max) test, hypercapnia, and recovery after VO2max test. The brain oxygenation and respiratory parameters of both sample sets were calculated using a non-parametric test (Mann-Whitney U test). Aerobic fitness outcome was quantified through mean average using the Bruce test. Participants performed Fitt's test using a laptop and analysis of medio-lateral and anterior-posterior range of oscillation was carried out via a force platform Romberg test. Results: mTBI group showed statistically significant differences in saturated hemoglobin Δ[HbO2] (p < 0.001) during rest and recovery phase after maximal incremental exercise, in medio-lateral sway eyes open (p = 0.008, NC 25.35 ± 4.11 mm and mTBI 17.65 ± 4.79 mm). VO2max revealed no significant differences between the two groups: NC 47.47 ± 4.91 mTBI 49.58 ± 5.19 ml/kg/min−1. The 2 groups didn't differ for maximum power output (NC 220 ± 34, mTBI 255 ± 50 W). End-tidal fractional concentration of O2 (FetO2 NC15.20 ± 0.41, mTBI 16.09 ± 0.68) throughout hypercapnia, saturated blood hemoglobin (Δ[HbO2]) revealed significant differences with the mTBI group. No differences emerged from Fitt's test. Conclusions: It emerges that NIRS is able to reveal differences in long time outcomes of mTBI. The medio-lateral variations cannot be considered as a marker of long-term damage in athletes specifically trained for balance.